2015
DOI: 10.1177/0959683615585840
|View full text |Cite
|
Sign up to set email alerts
|

Multi-centennial scale SST and Indian summer monsoon precipitation variability since the mid-Holocene and its nonlinear response to solar activity

Abstract: Indian Summer Monsoon (ISM) shows a weak correlation with solar variability in the 20th century. However, such climatological observations on solar activity-monsoon relationship are very short and hence uncertain. A few paleomonsoon records also exhibit prominent correspondence with solar activity during early Holocene and beyond. But despite the strong recent solar minima (e.g. Maunder, Spörer, Oort, Wolf), their correlation with monsoon precipitation is weak and inconclusive. Additionally, many of the earlie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 68 publications
4
32
0
Order By: Relevance
“…All original data and all calculations are presented as Tables S1 and S2 in the Supplement. In our compilation, temperature reconstructions from the eastern and southeastern Arabian Sea are based on Mg / Ca ratios of planktonic foraminifera (see methods in, e.g., Govil and Naidu, 2010;Mahesh and Banakar, 2014;Saraswat et al, 2013;Tiwari et al, 2015) except core MD90963, which has alkenone temperatures . All other records are alkenone temperatures calculated with the core top calibration of Sonzogni et al (1997b).…”
Section: Integration and Averaging Of Sst And δ 15 N Reconstructionsmentioning
confidence: 99%
“…All original data and all calculations are presented as Tables S1 and S2 in the Supplement. In our compilation, temperature reconstructions from the eastern and southeastern Arabian Sea are based on Mg / Ca ratios of planktonic foraminifera (see methods in, e.g., Govil and Naidu, 2010;Mahesh and Banakar, 2014;Saraswat et al, 2013;Tiwari et al, 2015) except core MD90963, which has alkenone temperatures . All other records are alkenone temperatures calculated with the core top calibration of Sonzogni et al (1997b).…”
Section: Integration and Averaging Of Sst And δ 15 N Reconstructionsmentioning
confidence: 99%
“…Thus, the nonconsistent long‐term trend of sedimentation rate observed in the present study is could be due to fewer numbers of dates and the same could be improved by dating few more number of samples in between to get a clear picture. Therefore, we note that, although there were few periods of enhanced SASM intensity, the long‐term trend shown by surface run‐off/detrital influx suggests decline in the SASM intensity since mid‐Holocene, which corroborates the previously determined decline in SASM precipitation [ Kessarkar et al ., ; Saraswat et al ., ; Tiwari et al ., ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the quantitative estimates of SASM intensity (based on δ 18 O of foraminifera, Mg/Ca, a proxy for seawater temperature) are limited and have coarse resolution [ Saraswat et al ., ; Anand et al ., ; Banakar et al ., ; Govil and Naidu , ; Saraswat et al ., ]. Recently, past salinity values determined from the same core used in the present study at a high‐resolution of centennial scale has shown declining SASM precipitation intensity since mid‐Holocene [ Tiwari et al ., ] (Figure j). This is further accompanied by the declining long‐term trend shown by Ti/Al (Figure i) in the present study, which suggests a decline in surface runoff/detrital influx with the declining SASM precipitation intensity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neff et al 2001;Fleitmann et al 2003;Gupta et al 2005;Wang et al 2005;Agnihotri et al 2011;Tiwari et al 2015;Xu et al 2015), from reanalysis data (e.g. Kodera 2004) and from modern observational data (e.g.…”
Section: Introductionmentioning
confidence: 99%